Preparation method of thermoplastic olefin elastomer
By using high melt strength polypropylene, linear low density polyethylene and ethylene-octene copolymer in thermoplastic olefin-based elastomers, and adding raw materials such as magnesium hydroxide, combined with kneading, refining, extrusion, calendering and coating agent wetting treatment, and finally compounding with the PPF foam layer, the existing thermoplastic olefin-based elastomers are solved, and the coordinated improvement of density, mechanics, flame retardant and weathering properties are achieved.
Patent Information
- Application Number
- CN202510136257.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-18
AI Technical Summary
When optimizing density, the existing thermoplastic olefin-based elastomers have poor mechanical properties, flame retardant properties, waterproofing and weathering stability, which limits the efficiency of the product.
High melt strength polypropylene, linear low density polyethylene and ethylene-octene copolymer are used as the main raw materials, and magnesium hydroxide, light stabilizer, stearic acid, antioxidant and modified filler are added. Thermoplastic olefin-based elastomer is prepared by kneading, refining, extrusion, calendering and coating agent wetting treatment, and finally combined with the PPF foam layer to prepare a thermoplastic olefin-based elastomer.
It significantly improves the density, mechanical properties and flame retardant properties of the product, and improves waterproof and weather resistance stability, improving the overall performance of the product.
Smart Images

Figure BDA0005263322140000141 
Figure BDA0005263322140000151 
Figure BDA0005263322140000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of olefin elastomers, and in particular to a method for preparing a thermoplastic olefin elastomer. Background Art
[0002] As global energy and environmental issues become increasingly serious, the pace of "lightweighting" of automotive materials has further accelerated. The selection of lightweight materials is the most effective way to lightweight automobiles. Under the condition of meeting the requirements, materials with lower density should be given priority. The standardization of automotive interior materials is an effective way to achieve recyclable and reusable materials. The types of automotive interior materials can be streamlined and the range of materials can be narrowed to: PP+EPDM, PP, ABS, PC+ABS, HDPE, etc. The standardization of vehicle materials and the standardization of components on different platforms are very beneficial to the recycling of scrapped vehicles.
[0003] In order to optimize the density of the product, the existing thermoplastic olefin elastomers easily lead to poor mechanical properties and flame retardancy of the product, as well as poor waterproof and weather resistance stability of the product, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a method for preparing a thermoplastic olefin elastomer to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a method for preparing a thermoplastic olefin elastomer, comprising the following steps:
[0007] Step 1: weigh the raw materials according to weight:
[0008] 38-42 parts of high melt strength polypropylene, 20-22 parts of linear low density polyethylene: 18-20 parts of ethylene-octene copolymer, 8-11 parts of magnesium hydroxide, 0.5-1 parts of light stabilizer, 0.1-0.3 parts of stearic acid, 0.2-0.5 parts of antioxidant, 2-5 parts of modified filler;
[0009] Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds;
[0010] Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min;
[0011] Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A;
[0012] Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C;
[0013] Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 10-15 MPa for 10 minutes, taken out, and dried to obtain an olefin elastomer;
[0014] Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
[0015] Preferably, the high melt strength polypropylene is made by the existing method in Chinese patent document CN108484810B;
[0016] The molar content of octene in the ethylene-octene copolymer is 45-50%, and the melting point of the ethylene-octene copolymer is 85° C.;
[0017] The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 1.5-2.0g / 10min, and the density is 0.918-0.921g / cm 3 .
[0018] Preferably, the preparation method of the modified filler is:
[0019] S11: preheating the hollow glass microspheres at 60-65° C. for 1 h, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying;
[0020] S12: adding the dried hollow glass microspheres to the dopamine-carbon nanotube solution having a total amount of 5-8 times the dried hollow glass microspheres, and stirring the solution, and obtaining a modified hollow glass microsphere agent after the stirring is completed;
[0021] S13: Preparation of ball formulation:
[0022] S131: 2-5 parts of rice husk ash, 4-6 parts of lanthanum chloride solution and 1-2 parts of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent;
[0023] S132: 1-3 parts of silane coupling agent KH550 and 2-4 parts of nano titanium dioxide are added to 5-8 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation;
[0024] S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain a modified filler agent.
[0025] Preferably, the stirring speed of the stirring treatment in S12 is 550-650 r / min, and the stirring is for 20-30 min; the ultrasonic power of the ultrasonic treatment in S132 is 450-500 W, and the ultrasonic treatment is for 1 h.
[0026] Preferably, the mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 2-4%.
[0027] Preferably, the preparation method of dopamine-carbon nanotube liquid is:
[0028] The carbon nanotubes are irradiated in a proton irradiation box for 10-15 minutes at an irradiation power of 350W. After the irradiation is completed, irradiated carbon nanotubes are obtained. 3-5 parts of irradiated carbon nanotubes, 1-2 parts of kaolin, and 0.2-0.4 parts of sodium silicate are added to 4-6 parts of dopamine hydrochloride solution, and then 0.1-0.3 parts of boron nitride are added and mixed evenly to obtain a dopamine-carbon nanotube solution.
[0029] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%.
[0030] Preferably, the preparation method of the finishing agent is:
[0031] S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 3-5 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid;
[0032] S12: 5-8 parts of water-emulsion polyurethane resin, 1-3 parts of polyethylene glycol, 2-4 parts of polycarbodiimide and 4-7 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
[0033] Preferably, the solid content of the water-emulsion polyurethane resin is 40-45%.
[0034] Preferably, the silane coupling agent is silane coupling agent KH560.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The olefin elastomer of the present invention adopts high melt strength polypropylene, linear low density polyethylene and ethylene-octene copolymer, and magnesium hydroxide, light stabilizer and stearic acid raw materials are added, and the modified filler is added to optimize the product performance. After kneading, open refining, extrusion and calendering and other processes, and then combined with a coating agent infiltration treatment, the obtained olefin elastomer product has coordinated improvement in density performance, mechanical performance and flame retardant performance, and the product has significant waterproof and weather resistance stability effects; the modified filler adopts hollow glass microspheres that are preheated and then treated with potassium permanganate solution to optimize its active efficiency, and then subjected to stirring treatment in a dopamine-carbon nanotube liquid to reconcile the synergistic effect of the hollow glass microspheres and the ball preparation, the ball preparation adopts silane coupling agent KH550, nano titanium dioxide is subjected to ultrasonic treatment of rice husk ash agent, and rice husk ash, lanthanum chloride solution and carboxymethyl in the rice husk ash agent are used to prepare the silane coupling agent KH550, and ... The synergistic effect of sodium cellulose is achieved through the coordination and coordination between the raw materials to enhance the loading effect of the hollow glass microsphere carrier, thereby strengthening the system performance effect and further improving the performance of the product; the dopamine-carbon nanotube liquid uses carbon nanotubes treated with proton irradiation, and then blended with kaolin, sodium silicate, dopamine hydrochloride solution and boron nitride. Through the synergistic effect of the co-formulation between the raw materials, the lamellar kaolin and the carbon nanotubes with a high specific surface area are blended in the system to optimize the system performance coordination and performance stability, and the performance of the product is further improved; the coating agent uses flaky talc treated with silane coupling liquid to optimize the interface of the flaky talc, which is convenient for better blending with raw materials such as water-emulsified polyurethane resin, so that it can be coated on the surface of the coil, and then compounded with the PPF foaming layer to optimize the performance stability and performance coordination of the coil. DETAILED DESCRIPTION
[0037] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] A method for preparing a thermoplastic olefin elastomer according to the present embodiment comprises the following steps:
[0039] Step 1: weigh the raw materials according to weight:
[0040] 38-42 parts of high melt strength polypropylene, 20-22 parts of linear low density polyethylene, 18-20 parts of ethylene-octene copolymer, 8-11 parts of magnesium hydroxide, 0.5-1 parts of light stabilizer, 0.1-0.3 parts of stearic acid, 0.2-0.5 parts of antioxidant, 2-5 parts of modified filler;
[0041] Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds;
[0042] Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min;
[0043] Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A;
[0044] Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C;
[0045] Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 10-15 MPa for 10 minutes, taken out, and dried to obtain an olefin elastomer;
[0046] Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
[0047] The high melt strength polypropylene of this embodiment is prepared by the method described in Chinese patent document CN108484810B;
[0048] The molar content of octene in the ethylene-octene copolymer is 45-50%, and the melting point of the ethylene-octene copolymer is 85° C.;
[0049] The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 1.5-2.0g / 10min, and the density is 0.918-0.921g / cm 3 .
[0050] The preparation method of the modified filler of this embodiment is:
[0051] S11: preheating the hollow glass microspheres at 60-65° C. for 1 h, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying;
[0052] S12: adding the dried hollow glass microspheres to the dopamine-carbon nanotube solution having a total amount of 5-8 times the dried hollow glass microspheres, and stirring the solution, and obtaining a modified hollow glass microsphere agent after the stirring is completed;
[0053] S13: Preparation of ball formulation:
[0054] S131: 2-5 parts of rice husk ash, 4-6 parts of lanthanum chloride solution and 1-2 parts of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent;
[0055] S132: 1-3 parts of silane coupling agent KH550 and 2-4 parts of nano titanium dioxide are added to 5-8 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation;
[0056] S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain a modified filler agent.
[0057] The stirring speed of the stirring treatment in S12 of this embodiment is 550-650r / min, and the stirring is performed for 20-30min; the ultrasonic power of the ultrasonic treatment in S132 is 450-500W, and the ultrasonic treatment is performed for 1h.
[0058] The mass fraction of the potassium permanganate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 2-4%.
[0059] The preparation method of the dopamine-carbon nanotube liquid of this embodiment is:
[0060] The carbon nanotubes are irradiated in a proton irradiation box for 10-15 minutes at an irradiation power of 350W. After the irradiation is completed, irradiated carbon nanotubes are obtained. 3-5 parts of irradiated carbon nanotubes, 1-2 parts of kaolin, and 0.2-0.4 parts of sodium silicate are added to 4-6 parts of dopamine hydrochloride solution, and then 0.1-0.3 parts of boron nitride are added and mixed evenly to obtain a dopamine-carbon nanotube solution.
[0061] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%.
[0062] The preparation method of the finishing agent of this embodiment is:
[0063] S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 3-5 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid;
[0064] S12: 5-8 parts of water-emulsion polyurethane resin, 1-3 parts of polyethylene glycol, 2-4 parts of polycarbodiimide and 4-7 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
[0065] The solid content of the water-emulsion polyurethane resin in this embodiment is 40-45%.
[0066] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0067] Example 1.
[0068] A method for preparing a thermoplastic olefin elastomer according to the present embodiment comprises the following steps:
[0069] Step 1: weigh the raw materials according to weight:
[0070] 38 parts of high melt strength polypropylene, 20 parts of linear low density polyethylene: 18 parts of ethylene-octene copolymer, 8 parts of magnesium hydroxide, 0.5 parts of light stabilizer, 0.1 parts of stearic acid, 0.2 parts of antioxidant, 2 parts of modified filler;
[0071] Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds;
[0072] Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min;
[0073] Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A;
[0074] Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C;
[0075] Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 10 MPa for 10 minutes, taken out and dried to obtain an olefin elastomer;
[0076] Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
[0077] The high melt strength polypropylene of this embodiment is prepared by the method described in Chinese patent document CN108484810B;
[0078] The molar content of octene in the ethylene-octene copolymer is 45%, and the melting point of the ethylene-octene copolymer is 85° C.;
[0079] The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 1.5g / 10min, and the density is 0.918g / cm 3 .
[0080] The preparation method of the modified filler of this embodiment is:
[0081] S11: preheating the hollow glass microspheres at 60° C. for 1 h, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying;
[0082] S12: adding the dried hollow glass microspheres to the dopamine-carbon nanotube solution having a total amount of 5 times the dried hollow glass microspheres, and stirring the solution, and obtaining a modified hollow glass microsphere agent after the stirring is completed;
[0083] S13: Preparation of ball formulation:
[0084] S131: 2 parts of rice husk ash, 4 parts of lanthanum chloride solution and 1 part of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent;
[0085] S132: 1 part of silane coupling agent KH550 and 2 parts of nano titanium dioxide are added to 5 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation;
[0086] S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler agent.
[0087] The stirring speed of the stirring treatment in S12 of this embodiment is 550 r / min, and the stirring is for 20 min; the ultrasonic power of the ultrasonic treatment in S132 is 450 W, and the ultrasonic treatment is for 1 h.
[0088] The mass fraction of the potassium permanganate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 2%.
[0089] The preparation method of the dopamine-carbon nanotube liquid of this embodiment is:
[0090] The carbon nanotubes were irradiated in a proton irradiation box for 10 min at an irradiation power of 350 W. After the irradiation was completed, irradiated carbon nanotubes were obtained. Three parts of irradiated carbon nanotubes, one part of kaolin, and 0.2 parts of sodium silicate were added to 4 parts of dopamine hydrochloride solution, and then 0.1 parts of boron nitride were added and mixed evenly to obtain a dopamine-carbon nanotube solution.
[0091] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%.
[0092] The preparation method of the finishing agent of this embodiment is:
[0093] S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 3 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid;
[0094] S12: 5 parts of water-emulsion polyurethane resin, 1 part of polyethylene glycol, 2 parts of polycarbodiimide and 4 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
[0095] The solid content of the water-emulsion polyurethane resin in this embodiment is 40%.
[0096] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0097] Example 2.
[0098] A method for preparing a thermoplastic olefin elastomer according to the present embodiment comprises the following steps:
[0099] Step 1: weigh the raw materials according to weight:
[0100] 42 parts of high melt strength polypropylene, 22 parts of linear low density polyethylene: 20 parts of ethylene-octene copolymer, 11 parts of magnesium hydroxide, 1 part of light stabilizer, 0.3 parts of stearic acid, 0.5 parts of antioxidant, 5 parts of modified filler;
[0101] Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds;
[0102] Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min;
[0103] Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A;
[0104] Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C;
[0105] Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 10-15 MPa for 10 minutes, taken out, and dried to obtain an olefin elastomer;
[0106] Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
[0107] The high melt strength polypropylene of this embodiment is prepared by the method described in Chinese patent document CN108484810B;
[0108] The molar content of octene in the ethylene-octene copolymer is 50%, and the melting point of the ethylene-octene copolymer is 85° C.;
[0109] The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 2.0g / 10min, and the density is 0.921g / cm 3 .
[0110] The preparation method of the modified filler of this embodiment is:
[0111] S11: preheating the hollow glass microspheres at 65°C for 1 hour, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying;
[0112] S12: adding the dried hollow glass microspheres to a dopamine-carbon nanotube solution having an amount of 8 times the total amount of the dried hollow glass microspheres and stirring the solution, and obtaining a modified hollow glass microsphere agent after the stirring is completed;
[0113] S13: Preparation of ball formulation:
[0114] S131: 5 parts of rice husk ash, 6 parts of lanthanum chloride solution and 2 parts of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent;
[0115] S132: 3 parts of silane coupling agent KH550 and 4 parts of nano titanium dioxide are added to 8 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation;
[0116] S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 11500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler agent.
[0117] The stirring speed of the stirring treatment in S12 of this embodiment is 650 r / min, and the stirring is for 30 min; the ultrasonic power of the ultrasonic treatment in S132 is 500 W, and the ultrasonic treatment is for 1 h.
[0118] The mass fraction of the potassium permanganate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 4%.
[0119] The preparation method of the dopamine-carbon nanotube liquid of this embodiment is:
[0120] The carbon nanotubes were irradiated in a proton irradiation box for 15 minutes at an irradiation power of 350 W. After the irradiation was completed, irradiated carbon nanotubes were obtained. Five parts of irradiated carbon nanotubes, 2 parts of kaolin, and 0.4 parts of sodium silicate were added to 6 parts of dopamine hydrochloride solution, and then 0.3 parts of boron nitride were added and mixed evenly to obtain a dopamine-carbon nanotube solution.
[0121] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%.
[0122] The preparation method of the finishing agent of this embodiment is:
[0123] S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 5 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid;
[0124] S12: 8 parts of water-emulsion polyurethane resin, 3 parts of polyethylene glycol, 4 parts of polycarbodiimide and 7 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
[0125] The solid content of the water-emulsion polyurethane resin in this embodiment is 45%.
[0126] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0127] Example 3.
[0128] A method for preparing a thermoplastic olefin elastomer according to the present embodiment comprises the following steps:
[0129] Step 1: weigh the raw materials according to weight:
[0130] 40 parts of high melt strength polypropylene, 21 parts of linear low density polyethylene: 19 parts of ethylene-octene copolymer, 9 parts of magnesium hydroxide, 0.85 parts of light stabilizer, 0.2 parts of stearic acid, 0.35 parts of antioxidant, 3.5 parts of modified filler;
[0131] Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds;
[0132] Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min;
[0133] Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A;
[0134] Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C;
[0135] Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 12.5 MPa for 10 minutes, taken out, and dried to obtain an olefin elastomer;
[0136] Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
[0137] The high melt strength polypropylene of this embodiment is prepared by the method described in Chinese patent document CN108484810B;
[0138] The molar content of octene in the ethylene-octene copolymer is 47.5%, and the melting point of the ethylene-octene copolymer is 85° C.;
[0139] The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 1.8g / 10min, and the density is 0.920g / cm 3 .
[0140] The preparation method of the modified filler of this embodiment is:
[0141] S11: preheating the hollow glass microspheres at 62.5°C for 1 hour, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying;
[0142] S12: adding the dried hollow glass microspheres to the dopamine-carbon nanotube solution having a total amount of 6.5 times the dried hollow glass microspheres, and stirring the solution until the stirring is completed, thereby obtaining a modified hollow glass microsphere agent;
[0143] S13: Preparation of ball formulation:
[0144] S131: 3.5 parts of rice husk ash, 5 parts of lanthanum chloride solution and 1.5 parts of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent;
[0145] S132: 2 parts of silane coupling agent KH550 and 3 parts of nano titanium dioxide are added to 6.5 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation;
[0146] S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1250 r / min for 1 h. After the ball milling is completed, the modified filler agent is filtered and dried to obtain the modified filler agent.
[0147] The stirring speed of the stirring treatment in S12 of this embodiment is 600 r / min, and the stirring is for 25 min; the ultrasonic power of the ultrasonic treatment in S132 is 470 W, and the ultrasonic treatment is for 1 h.
[0148] The mass fraction of the potassium permanganate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 3%.
[0149] The preparation method of the dopamine-carbon nanotube liquid of this embodiment is:
[0150] The carbon nanotubes were irradiated in a proton irradiation box for 12.5 min at an irradiation power of 350 W. After the irradiation was completed, irradiated carbon nanotubes were obtained. 4 parts of irradiated carbon nanotubes, 1.5 parts of kaolin, and 0.3 parts of sodium silicate were added to 5 parts of dopamine hydrochloride solution, and then 0.2 parts of boron nitride were added and mixed evenly to obtain dopamine-carbon nanotube solution.
[0151] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%.
[0152] The preparation method of the finishing agent of this embodiment is:
[0153] S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 4 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid;
[0154] S12: 6.5 parts of water-emulsion polyurethane resin, 2 parts of polyethylene glycol, 3 parts of polycarbodiimide and 5.5 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
[0155] The solid content of the water-emulsion polyurethane resin in this embodiment is 42.5%.
[0156] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0157] Comparative Example 1.
[0158] The difference from Example 3 is that no modified filler is added.
[0159] Comparative Example 2.
[0160] The difference from Example 3 is that no spherical compounding agent is added in the preparation of the modified filler.
[0161] Comparative Example 3.
[0162] The difference from Example 3 is that no rice husk ash is added in the preparation of the ball formulation.
[0163] Comparative Example 4.
[0164] The difference from Example 3 is that the rice husk ash agent is directly replaced by the rice husk ash raw material.
[0165] Comparative Example 5.
[0166] The difference from Example 3 is that no silane coupling agent KH550 and nano titanium dioxide are added in the preparation of the ball formulation.
[0167] Comparative Example 6.
[0168] The difference from Example 3 is that no modified hollow glass microspheres are added in the preparation of the modified filler.
[0169] Comparative Example 7.
[0170] The difference from Example 3 is that no dopamine-carbon nanotube liquid is added in the preparation of the modified hollow glass microspheres.
[0171] Comparative Example 8.
[0172] The difference from Example 3 is that no finishing agent treatment is used.
[0173] Comparative Example 9.
[0174] The difference from Example 3 is that no flaky talc liquid is added to the finishing agent.
[0175] The products of Examples 1 to 3 and Comparative Examples 1 to 9 were subjected to performance tests to test the density, mechanical properties and flame retardancy of the products, as well as the waterproof and weathering stability of the products (the products were immersed in 65°C water for 48 hours and then irradiated with UV light for 12 hours with a UV intensity of 100w / m 2 , the above is a cycle, cycle 10 times), the test results are as follows;
[0176]
[0177]
[0178] It can be seen from Comparative Examples 1 to 9 and Examples 1 to 3 that;
[0179] The product of Example 3 has excellent low density, and at the same time, excellent longitudinal tensile strength and limiting oxygen index performance, and the three can be improved in a coordinated manner. In addition, the product has excellent performance under waterproof and weather resistance conditions, and the product can achieve integrated coordinated improvement and performance stability improvement;
[0180] From Comparative Examples 1 to 9 and Example 3, it can be seen that the product does not add modified fillers, the density is reduced, but not significantly, and the longitudinal tensile strength and limiting oxygen index change poorly. Without the use of a finishing agent, the density, longitudinal tensile strength, and limiting oxygen index of the product all have a significant deterioration trend;
[0181] The modified filler and finishing agent are used for treatment. The two cooperate with each other and work together to achieve the most significant performance effect of the product. No ball preparation agent is added in the preparation of the modified filler, no rice husk ash agent is added in the preparation of the ball preparation, the rice husk ash agent is directly replaced by rice husk ash raw materials, no silane coupling agent KH550 and nano titanium dioxide are added in the preparation of the ball preparation, no modified hollow glass microsphere agent is added in the preparation of the modified filler, and no dopamine-carbon nanotube liquid is added in the preparation of the modified hollow glass microsphere agent. The performance of the product has a tendency to deteriorate to varying degrees. Without the addition of dopamine-carbon nanotube liquid, the performance of the product deteriorates more significantly.
[0182] The modified filler prepared by combining the ball formulation obtained by the specific method of the present invention with the modified hollow glass microsphere agent has the most significant performance effect. The performance effect of the product is not as obvious as that of the present invention when other methods are used instead. The performance effect of the product also tends to deteriorate when no flaky talcum powder liquid is added to the coating agent.
[0183] Based on the fact that dopamine-carbon nanotube liquid has a significant impact on the performance of the product, further research is conducted on this:
[0184] Experimental example 1.
[0185] The only difference from Example 3 is that no irradiated carbon nanotubes are added to the dopamine-carbon nanotube solution.
[0186] Experimental example 2.
[0187] The only difference from Example 3 is that no kaolin is added to the dopamine-carbon nanotube solution.
[0188] Experimental Example 3.
[0189] The only difference from Example 3 is that no sodium silicate is added to the dopamine-carbon nanotube solution.
[0190] Experimental Example 4.
[0191] The only difference from Example 3 is that no boron nitride is added to the dopamine-carbon nanotube solution.
[0192] Experimental Example 5.
[0193] The only difference from Example 3 is that the dopamine hydrochloride solution is replaced by water.
[0194]
[0195] It can be seen from Experimental Examples 1-5 that kaolin was not added to the dopamine-carbon nanotube solution, and the product had the greatest performance degradation trend under the conditions of the stability test, followed by the absence of boron nitride. At the same time, when no irradiated carbon nanotubes were added to the dopamine-carbon nanotube solution, no sodium silicate was added to the dopamine-carbon nanotube solution, and water was used instead of the dopamine hydrochloride solution, the performance of the products all tended to deteriorate. Only the product prepared using the specific raw materials of the present invention had the most significant performance effect, and other methods were not as obvious as the effect of the present invention.
[0196] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0197] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a thermoplastic olefin elastomer, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: 38-42 parts of high melt strength polypropylene, 20-22 parts of linear low density polyethylene, 18-20 parts of ethylene-octene copolymer, 8-11 parts of magnesium hydroxide, 0.5-1 parts of light stabilizer, 0.1-0.3 parts of stearic acid, 0.2-0.5 parts of antioxidant and 2-5 parts of modified filler; Step 2: kneading, using high speed, high temperature and high shear force to polymerize the materials in step 1, the kneading machine temperature is 130°C, and the material making time is 660 seconds; Step 3: refining, using an open mill for melting and plasticization, the temperature of the open mill is 160° C., the gap is 3 cm, and the speed is 30 m / min; Step 4: extrusion, plasticization using a single screw extruder, barrel temperature 155°C, die temperature 150°C, screw speed 60 rpm, current ≤95A; Step 5: calendering: the four-roll calender calenders the product of step 4 into a coil of required width and thickness, with the front roll temperature of 165°C, the upper roll temperature of 165°C, the middle roll temperature of 160°C, the lower roll temperature of 155°C, and the take-up temperature of 150°C; Step 6: The coiled material of step 5 is soaked in a sufficient amount of the finishing agent at a soaking pressure of 10-15 MPa for 10 minutes, taken out, and dried to obtain an olefin elastomer; Step seven, finally, the olefin elastomer and the PPF foaming layer are compounded by a heat bonding process, the thickness of the PPF foaming layer is 1 mm, the preheating temperature of the PPF foaming layer is 90° C., and the temperature of the olefin elastomer is 150° C., to obtain the thermoplastic olefin elastomer of the present invention.
2. The method for preparing a thermoplastic olefin elastomer according to claim 1, characterized in that: The high melt strength polypropylene is made by the method disclosed in Chinese patent document CN108484810B; The molar content of octene in the ethylene-octene copolymer is 45-50%, and the melting point of the ethylene-octene copolymer is 85° C.; The light stabilizer is UV absorber UV327; the antioxidant is antioxidant 1010; the melt mass flow rate (190°C, 2.16kg) of the linear low-density polyethylene is 1.5-2.0g / 10min, and the density is 0.918-0.921g / cm 3 .
3. The method for preparing a thermoplastic olefin elastomer according to claim 1, characterized in that: The preparation method of the modified filler is: S11: preheating the hollow glass microspheres at 60-65° C. for 1 h, then stirring the preheated hollow glass microspheres in a sufficient amount of potassium permanganate solution, and then washing, filtering, and drying; S12: adding the dried hollow glass microspheres to the dopamine-carbon nanotube solution having a total amount of 5-8 times the dried hollow glass microspheres, and stirring the solution, and obtaining a modified hollow glass microsphere agent after the stirring is completed; S13: Preparation of ball formulation: S131: 2-5 parts of rice husk ash, 4-6 parts of lanthanum chloride solution and 1-2 parts of sodium carboxymethyl cellulose are uniformly mixed to obtain a rice husk ash agent; S132: 1-3 parts of silane coupling agent KH550 and 2-4 parts of nano titanium dioxide are added to 5-8 parts of rice husk ash for ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain a spherical formulation; S14: The modified hollow glass microsphere agent and the ball agent are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain a modified filler agent.
4. The method for preparing a thermoplastic olefin elastomer according to claim 3, characterized in that: The stirring speed of the stirring treatment in S12 is 550-650 r / min, and the stirring is performed for 20-30 min. The ultrasonic power of the ultrasonic treatment in S132 is 450-500 W, and the ultrasonic treatment is performed for 1 h.
5. The method for preparing a thermoplastic olefin elastomer according to claim 3, characterized in that: The mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 2-4%.
6. The method for preparing a thermoplastic olefin elastomer according to claim 3, characterized in that: The preparation method of dopamine-carbon nanotube liquid is as follows: The carbon nanotubes are irradiated in a proton irradiation box for 10-15 minutes at an irradiation power of 350W. After the irradiation is completed, irradiated carbon nanotubes are obtained. 3-5 parts of irradiated carbon nanotubes, 1-2 parts of kaolin, and 0.2-0.4 parts of sodium silicate are added to 4-6 parts of dopamine hydrochloride solution, and then 0.1-0.3 parts of boron nitride are added and mixed evenly to obtain a dopamine-carbon nanotube solution.
7. The method for preparing a thermoplastic olefin elastomer according to claim 6, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%.
8. The method for preparing a thermoplastic olefin elastomer according to claim 1, characterized in that: The preparation method of the finishing agent is: S11: mixing a silane coupling agent, deionized water and ethanol in a weight ratio of 3:5:2 to obtain a silane coupling liquid; stirring the flaky talc powder in the silane coupling liquid in an amount of 3-5 times the total amount of the flaky talc powder to obtain a flaky talc powder liquid; S12: 5-8 parts of water-emulsion polyurethane resin, 1-3 parts of polyethylene glycol, 2-4 parts of polycarbodiimide and 4-7 parts of flaky talc liquid are uniformly blended to obtain a finishing agent.
9. The method for preparing a thermoplastic olefin elastomer according to claim 8, characterized in that: The solid content of the water-emulsion polyurethane resin is 40-45%.
10. The method for preparing a thermoplastic olefin elastomer according to claim 8, characterized in that: The silane coupling agent is silane coupling agent KH560.
Citation Information
Patent Citations
A method for preparing high melt strength polypropylene
CN108484810B